Oncocercose entre os índios Yanomámi Onchocerciasis among Yanomámi Indians - Mário A. P. Moraes (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1991)
Apresentam-se os dados até agora obtidos sobre o foco brasileiro de oncocercose. Esse foco, localizado no extremo norte do país, envolve principalmente indígenas do grupo Yanomámi, antigos habitantes do local. Em algumas aldeias, a infecção é encontrada em cerca de 80% dos adultos. Aspectos interessantes, como a origem do foco, as características da doença nos indígenas e os principais vetores de Onchocerca volvulus, são abordados. Por fim, é feita uma análise a respeito do comportamento da endemia e da possível disseminação da doença para outras regiões do Brasil - em áreas de garimpo. Sugerem-se medidas de controle, entre elas o uso de larvicidas, método que poderia ser adotado em lugares restritos - com população já estabilizada -, dentro da zona onde mais forte é a prevalência. The main features of the Brazilian focus of onchocerciasis are reported. This focus encompasses large areas of the states of Amazonas and Roraima, in the densely forested highlands of Northern Brazil. It is not clear how the local inhabitants, Indians of the group Yanomámi, an isolated group that has lived in the region for centuries, acquired the infection. However, in some of their villages the prevalence rate among adults is as high as 80%. Aspects of the focus, as its origins, manifestations of the illness among the Indians, and the distribution and importance of the recognized vectors of O. volvulus in the region, are reviewed. The author also makes some considerations on the behavior and probable future of the focus, including the possible dissemination of onchocerciasis to some other sites of Brazil. Gold miners that in recent years have invaded the Yanomámi territory and became infected in contact with the Indians will be the cause of this dissemination. Methods for controlling onchocerciasis are discussed and, besides the treatment of the infected Indians with Ivermectin, it is proposed the use of larvicides to eliminate the vectors. This method would be employed in some limited areas where the population is already stable and shows a very high prevalence rate.